P016 META-ANALYSIS OF DIETARY INTERVENTION EFFECTS IN CROHN'S DISEASE AND ULCERATIVE COLITIS. (7th February 2019) - DuBois, Kelli E; Beets, Michael; Blake, Christine; McCabe, Jennifer
Abstract: Background: Inflammatory Bowel Disease (IBD) is becoming a global health issue as incidence rates are rising throughout the world. The two most common inflammatory bowel diseases are Crohn's Disease (CD) and Ulcerative Colitis (UC). The main goal of medical treatment for IBD is to reduce symptoms and induce a state of remission by regulating the immune system with pharmaceutical therapies. For many individuals, medication alone is insufficient to maintain remission and live a 'normal' life. Diet is believed to play a significant role in disease management, but the effect of diet as treatment for CD and UC is unknown. This meta-analysis seeks to assess the collective effectiveness of dietary interventions on health outcomes related to Crohn's Disease and Ulcerative Colitis. Methods: A literature search was conducted using PubMed, Web of Science, and Medline (Ovid). Search terms included 'Crohn's Disease', 'Ulcerative Colitis', 'Inflammatory Bowel Disease', 'Nutrition', 'Diet', 'Dietary Treatment', and 'Intervention'. Randomized controlled trials and observational studies with human subjects were included. Studies on irritable bowel syndrome, enteral or parental nutrition therapy, or food-related supplements were excluded. Outcome measures were categorized as either clinical measures or patient-reported outcomes. A meta-analysis calculated an overall summary effect size with a moderator analysis assessing differences in effects for clinical measures versus patient-reported outcomes. Results: Twenty three studies were identified as eligible for inclusion. A summary effect size of 0.716 (95% CI, 0.379-1.054) indicates a moderately large positive effect. A positive effect size implies dietary interventions improve disease conditions, indicated by fewer symptoms, decreased inflammation, and decreased activity index scores. Moderator analysis showed effect sizes of 0.630 (95% CI, 0.257-1.004) and 0.878 (95% CI, 0.553-1.204) for clinical measures and patient reported outcomes, respectively. Conclusions: Findings suggest that while diet positively impacts IBD overall, individuals may perceive greater disease improvement than clinical measures suggest. This may be due to the effects of healthier food choices on overall health and well-being. These findings suggest a need for increased attention to the dietary lifestyles of individuals with Inflammatory Bowel Diseases and support for diet-based interventions among this population. Implementing dietary changes may lead to improved disease conditions, greater success in maintaining remission, and increased quality of life.